1904
DOI: 10.2307/1775749
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Physical Geography

Abstract: The authors have striven to adapt this l)0()k to tlie cai'liiT sta.ixes of the high-school cnurse.'J'(j this end the statements are simple, techuieal terms are sparingly used, and when employed they are prom[)tly defined. Thus a}iproaehed, Physieal Geography may well serve to introduce young students to the sjiirit and method of science.The aim of the volume as thus set forth "will ex})laiu the omission of a few of the more dihicult eonce})tions of land physiography w'hicli ajipear in some school texts.The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The diverse plan view shapes of rocky coastlines (broadly defined here as a cliff‐backed coast consisting of rock or well‐consolidated sediments) have long been a topic of scientific and general interest [ Gilbert and Brigham , ; Johnson , ]. A quick look at Google Earth reveals rocky coastline shapes ranging from crenulated to straight, with headlands interspersed with smooth sediment‐filled (and sediment‐free) embayments (Figure ); cross‐shore relief, or amplitude, of rocky coastlines varies from nearly zero to several thousand meters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse plan view shapes of rocky coastlines (broadly defined here as a cliff‐backed coast consisting of rock or well‐consolidated sediments) have long been a topic of scientific and general interest [ Gilbert and Brigham , ; Johnson , ]. A quick look at Google Earth reveals rocky coastline shapes ranging from crenulated to straight, with headlands interspersed with smooth sediment‐filled (and sediment‐free) embayments (Figure ); cross‐shore relief, or amplitude, of rocky coastlines varies from nearly zero to several thousand meters.…”
Section: Introductionmentioning
confidence: 99%
“…Early observers of rocky coastlines suggested that exposed headlands, if rock strength was constant alongshore, would be continually reduced in cross‐shore amplitude by wave impacts until the coastline reached a straight, featureless equilibrium configuration [ Gilbert and Brigham , ; Johnson , ]. It was also recognized early on that alongshore variations in rock strength, or resistance to incoming wave energy, could allow higher curvature coastline shapes to persist [ Gulliver , ; Johnson , ; Trenhaile , ], and this view is still predominant as many workers have attributed rocky coast morphology over a range of spatial scales, from shore platforms to headlands, to variations in rock strength [ Trenhaile , ; Benumof et al ., ; Trenhaile , ; Dickson et al ., ; Davies et al ., ; Kennedy and Dickson , ; Thornton and Stephenson , ; Naylor and Stephenson , ; Stephenson and Naylor , ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly should the student of Geology come the better to know the world in which he lives; to love its natural scenery because he understands it; to see meaning in its rocks and fossils and in the materials furnished by the earth's crust to the common arts of man. (Martin, 1930: 82) Martin's assessment of Gilbert and Brigham (1902) was that:…”
Section: Brigham As Popularizermentioning
confidence: 99%
“…Brigham also wrote A Text-Book of Geology (1900), Geographic Influences in American History (1903), Student's Laboratory Manual of Physical Geography (1905), From Trail to Railway through the Appalachians (1907) and Commercial Geography (1910). He co-authored An Introduction to Physical Geography with Grove Karl Gilbert (1902) (see Acknowledgements for complete bibliography source).…”
Section: Introductionmentioning
confidence: 99%